Research Trends in PjBL (Project-Based Learning) at Indonesian Journal of Biology Education - Mega Elvianasti; Festiyed; Yerimadesi; Eka Kartikawati; Zulherman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
Project-based learning (PjBL) was one of the learning strategies that can develop students' scientific skills in the 21st century. This study used a qualitative approach by analyzing several articles published in biology education journals in Indonesia from 2015–2022, focusing on studying the implementation of project-based learning on biological materials. The current study reveals that there has been a decline in the number of publications over the past four years. Among these studies, the dominant research design is quantitative. In addition, high school students and environmental content were the most targeted subjects and content, respectively. ANOVA and tests are the most commonly used data analysis techniques and instruments. Meanwhile, the most widely measured skills as learning outcomes are critical and creative thinking. Based on what this study found, a number of suggestions have been made to do more research on PjBL and to test other 21st century skills. Keywords:  Project Based Learning, Biology Education, Research Trends